Answer: x=26
Step-by-step explanation:
Answer:
Option C
Step-by-step explanation:
(7x^3y^3)^2
= (7)^2 * (x^3)^2 * (y^3)^2
= 49 * x^(3*2) * y^(3*2)
= 49x^6y^6
You have to distribute the terms in "7x^3 * y^3" each to the power of 2
(7)^2 * (x^3)^2 * (y^3)^2
Now you can apply the rule "(x^a)^b = x^a*b" and further simplify the expression
Answer:
![2(x-1)^{2}=4](https://tex.z-dn.net/?f=2%28x-1%29%5E%7B2%7D%3D4)
Step-by-step explanation:
<u><em>The options of the question are</em></u>
2(x − 1)2 = 4
2(x − 1)2 = −4
2(x − 2)2 = 4
2(x − 2)2 = −4
we have
![2x^{2} -4x-2=0](https://tex.z-dn.net/?f=2x%5E%7B2%7D%20-4x-2%3D0)
This is a vertical parabola open upward
The vertex represent the minimum value
The quadratic equation in vertex form is
![y=a(x-h)^2+k](https://tex.z-dn.net/?f=y%3Da%28x-h%29%5E2%2Bk)
where
a is a coefficient
(h,k) is the vertex
so
Convert the quadratic equation in vertex form
Factor 2 leading coefficient
![2(x^{2} -2x)-2=0](https://tex.z-dn.net/?f=2%28x%5E%7B2%7D%20-2x%29-2%3D0)
Complete the squares
![2(x^{2} -2x+1)-2-2=0](https://tex.z-dn.net/?f=2%28x%5E%7B2%7D%20-2x%2B1%29-2-2%3D0)
![2(x^{2} -2x+1)-4=0](https://tex.z-dn.net/?f=2%28x%5E%7B2%7D%20-2x%2B1%29-4%3D0)
Rewrite as perfect squares
![2(x-1)^{2}-4=0](https://tex.z-dn.net/?f=2%28x-1%29%5E%7B2%7D-4%3D0)
The vertex is the point (1,-4)
Move the constant to the right side
![2(x-1)^{2}=4](https://tex.z-dn.net/?f=2%28x-1%29%5E%7B2%7D%3D4)
Just like you drew those dotted lines. You know how to find the areas of rectangles which is A=length x width
The answer would be 20cm^2+6cm^2+18cm^2=44 cm^2
1, 3 and 4.
1. 3,6>0,9
2. 3,6<4,725
3. 3,6>1,575
4. 3,6>0,54